Aktivitas Antioksidan Kulit Buah Cempedak (Artocarpus integer (Thunb.) Merr.) asal Kalimantan Selatan - Ali Rakhman Hakim; Rina Saputri; Amanda Shelvia Savitri; Anisa Ujuldah; Fitri Sadlia (Jurnal Surya Medika (JSM), 2022)
The increasing incidence of diseases related to oxidative stress among the human population has led to an increase in the consumption of natural antioxidants in the human diet. The purpose of this study was to determine the antioxidant activity of cempedak fruit skin extract with 50% ethanol and 70% ethanol as solvents. The method used was testing of radical inhibitory activity with the DPPH method (1,1-diphenyl-picrylhydrazil) and as a positive control was vitamin C. The results of phytochemical screening were known to contain phenolics, flavonoids, and tannins. The results of the antioxidant activity of E50% obtained IC50 values of 650.07 ppm and IC50 of E70 of 1219.69 ppm. From these results, it can be concluded that the skin of the cempedak fruit does not have antioxidant activity.